(untitled) (Journal of Population and Development, 2022)
Sexual harassment is widespread and common issue. It is connected with unwelcome behavior within men and women on sex. The objective of this study was to plot perceptions and experiences of sexual harassment among educated female. This study was based on Secondary Education Examination (SEE) completed female aged 16 years and above by using self-administered questionnaire in Kathmandu. Total 250 females were selected and chi-square test was used for testing the association. More than a tenth respondents who were teachers/ lecturers said that SH is extremely problematic at community, workplace and school. Overwhelming majority of women (82%) experienced at least one form of sexual harassment. Study found that respondents’ age group was significantly associated (P<0.01) with experienced at least one place of sexual harassment. Similarly, married women experienced higher rate (80%) in at least one place of sexual harassment than unmarried women (75%). Therefore, this study suggests that sexual harassment among educated female in Kathmandu valley is prevalent and online harassment is also emerging. On the other hand, they do not want to expose and perceive it as a sexual harassment. Therefore, effective programs and policies related with sexual harassment needs to be addressed.